Citizenship Training: Youth and Social Action - Ana Corina Fernández Alatorre (Universidad Autónoma de Baja California, 2014)
The findings in this article provide conclusions from a larger research study, which utilized data from "life stories" and focus groups of young adults who lack access to social mobility. This study proposes to explore how the personal experiences of young adults who, voluntarily, became active participants of a collective action organization are connected to the shaping of their civic engagement. The interviewees are founders of an organization for the development of educational intervention projects that seek the collective participation of young adults from marginalized communities. The findings reveal how formative development affect their personal citizenship experiences, as well as ignite a commitment to social action.